The effects of neutral gas heating on H mode transition and maintenance currents in a 13.56 MHz planar coil inductively coupled plasma reactor - Jayapalan, K.K.; Chin, Oi Hoong (2012)
The H mode transition and maintenance currents in a 13.56 MHz laboratory 6 turn planar coil inductively coupled plasma (ICP) reactor are simulated for low pressure argon discharge range of 0.02-0.3 mbar with neutral gas heating and at ambient temperature. An experimentally fitted 3D power evolution plot for 0.02 mbar argon pressure is also shown to visualize the effects of hysteresis in the system. Comparisons between simulation and experimental measurements show good agreement in the pressure range of 0.02-0.3 mbar for transition currents and 0.02-0.1 mbar for maintenance currents only when neutral gas heating is considered. This suggests that neutral gas heating plays a non-negligible role in determining the mode transition points of a rf ICP system.